A RETROSPECTIVE COHORT STUDY ON THE RISK FACTORS OF GASTROINTESTINAL BLEEDING IN ACUTE ISCHEMIC STROKE PATIENTS WITH ATRIAL FIBRILLATION - Rizaldy Taslim Pinzon (Romanian Journal of Neurology, 2021)
Introduction. Gastrointestinal (GI) bleeding is a serious complication of stroke causing high morbidity. Atrial fibrillation is associated with both ischemic stroke and GI bleeding due to usage of anticoagulant. The aim of this study is to determine the risk factors of GI bleeding in ischemic stroke patients with atrial fibrillation. Material and methods. All ischemic stroke patients with atrial fibrillation from January 2017 to December 2018 were extracted from our hospital-based stroke registry. We extracted demographical characteristic, subtypes of stroke, and medication history. Results. We found 96 ischemic stroke patients with AF were included in the study. Dyslipidemia (RR: 0.2; 95%CI: 0.043-0.939; p = 0.049) and antihyperlipidemic drugs (RR: 0.183; 95%CI: 0.039-0.857; p = 0.022) was associated with lower GI bleeding risk. There were no significant association between other risk factors and GI bleeding incidence Conclusion. Our research shows that dyslipidemia and history of antihyperlipidemic drugs are associated with lower GI bleeding risk in ischemic stroke patients with AF.